Implementasi Model Pembelajaran Sport Education Dalam Permainan Menggiring Bola Untuk Meningkatkan Kemampuan Gerak Siswa Pada Materi Tematik - Wiwit Santoso; Asep Sunarko; Luluk Alawiyah (STAI AL-AMIN, 2025)
This article discusses the Sport Education learning model and its impact on elementary school students, analyzes the improvement of class V students' movement skills at SDN 2 Kalibening in dribbling through this model and identifies the supporting and inhibiting factors for its application. The method uses a descriptive quantitative approach and field research with an evaluation design. Data were collected through observation, questionnaires, documentation, and interviews with the Head and Mentors of Kampung Sains. The analysis used descriptive statistics (percentage) and discrepancy model. Sport Education proved effective in improving students' movement skills and forming positive characters (responsibility, cooperation, sportsmanship), as well as developing cognitive, affective, and psychomotor domains in a balanced manner. The average score increased by 15.5 points from pretest to posttest, with the dominant student assessment in the good category. Supporting and inhibiting factors for success were influenced by student enthusiasm, the role of the teacher, adequate facilities, and time management. Obstacles such as limited time, weather, and role adaptation can be overcome through teacher strategies. The Sport Education model is effective and feasible to be developed in learning PJOK in elementary schools.